Activating Calcium-Sensing Receptor Mutations: Prospects for Future Treatment with Calcilytics - Mayr, Bernhard; Glaudo, Markus; Schöfl, Christof (Trends in Endocrinology and Metabolism, 2016)
Activating mutations of the G protein-coupled receptor, calcium-sensing receptor (CaSR), cause autosomal dominant hypocalcemia and Bartter syndrome type 5. These mutations lower the set-point for extracellular calcium sensing, thereby causing decreased parathyroid hormone secretion and disturbed renal calcium handling with hypercalciuria. Available therapies increase serum calcium levels but raise the risk of complications in affected patients. Symptom relief and the prevention of adverse outcome is currently very difficult to achieve. Calcilytics act as CaSR antagonists that attenuate its activity, thereby correcting the molecular defect of activating CaSR proteins in vitro and elevating serum calcium in mice and humans in vivo, and have emerged as the most promising therapeutics for the treatment of these rare and difficult to treat diseases.
EVALuna2:2214